Prediction of Viable CD34 Count in Harvested Product by Peripheral Blood Hematopoietic Progenitor Count of Automated Hematology Analyzer Undergoing Hematopoietic Stem Cell Transplantation - Siew Lian Chong; Asral Wirda Ahmad Asnawi; Tengku Amatullah Madeehah Tengku Mohd; Sen Mui Tan (Dovepress, 2024)
Indexed by WOS/Scopus